“Pero ¿de qué habla?”: un examen sobre lo que sea la ética a partir de su objeto de estudio - Alarco Grijalva, Abel de Dios (2021)
We assume that the question “what is ethics?” implies an ontological and metaontological research, fact which should lead us to an explanation and justification of the naturalistic research program. Under such framework, an ontological research should favorably proceed if it’s unrestricted and epistemically responsible with providing criteria. In such case, the ontology of something could be called a porttheory, which, in regard to ethics and this case, would be delimited to the examination of metaethical stances and to the definition of “ethics” by the definition of its subjectmatter. The examination will result in noting the apparent un-encompassing character of morality, which could lead to an abolitionism based on its conceptual fatigue. We object such abolitionism by affirming that the ampleness of what’s moral, in his metaethical presentation, calls for a better accordance with naturalism.